Irisin and Bone: From Preclinical Studies to the Evaluation of Its Circulating Levels in Different Populations of Human Subjects - Graziana Colaianni; Lorenzo Sanesi; Giuseppina Storlino; Giacomina Brunetti; Silvia Colucci; Maria Grano (Cells, 2019)
Almost four years after the discovery of the anabolic action of irisin on bone in mice, ample clinical evidence is emerging in support of its additional physiological relevance in human bone. Irisin inversely correlates with sclerostin levels in adults with prediabetes and with vertebral fragility fractures in post-menopausal women. Furthermore, in athletes we observed a positive correlation between irisin and bone mineral density at different anatomical sites. Our group also described a positive association between serum irisin and bone status in healthy children and multivariate regression analysis showed that irisin is a stronger determinant of bone mineral status than bone alkaline phosphatase. In children with type 1 diabetes mellitus, serum irisin concentrations are positively associated with bone quality and with glycemic control following continuous subcutaneous insulin infusion. Additionally, our in vitro studies suggest the existence of a negative interplay between PTH and irisin biology and these results were also supported by the observation that post-menopausal women with primary hyperparathyroidism have lower levels of irisin compared to matched controls. In this review, we will focus on recent findings about circulating level of irisin in different populations of human subjects and its correlation with their bone status.